CORRELATION JUNIOR HIGH SCHOOL STUDENT’S LEARNING MOTIVATION AND MATHEMATICS-CREATIVE THINKING ABILITY IN KABUPATEN ACEH BARAT - Lili Handayani; Siti Mayang Sari; Akmaluddin; Jonni Sitorus (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
The research aims are as follows: describing the student's learning motivationand mathematics-creative thinking ability; testing their correlations; andcalculating the contribution percentage of the learning motivation to theincrease in the student’s mathematics-creative thinking ability. The total samplesize is 620 students from ten junior high schools. Data was collected by twomethods, as follows: a questionnaire and a test. There are sixteen questions inthe learning motivation questionnaire and one open-ended question on thestudent’s mathematics creative thinking ability test. The data is analysedquantitatively. The correlation between the learning motivation and thestudents’ mathematics-creative thinking ability was analysed by using PearsonProduct-Moment Correlation with ⍺ = 5% and N = 620. The research showedthat the learning motivation and five of the its indicators have positive andsignificant correlations and have contributed to the increase with a student’smathematics creativity ability and the three of its indicators.